AKIBAT HUKUM RESIKO MEDIK DALAM PELAYANAN MEDIS TERHADAP PASIEN OLEH TENAGA MEDIS ( Analisis Putusan Nomor 13/Pdt.G/2020/PN Mrt ) - Salamah (ALWAQFU: Jurnal Hukum Ekonomi dan Wakaf, 2024)
Medical risk means that in medical actions carried out on patients there is a possibility (risk) that could occur. Examples of medical risks include: (1) inherent risks (hair loss due to administration of cytostatics/drugs that kill cancer cells); (2) hypersensitivity reactions, for example an excessive/deviant immune response to the introduction of foreign substances/drugs that are often unpredictable; (3) complications/difficulties that occur suddenly and cannot be predicted beforehand (amniotic fluid embolism in the mother during childbirth). Based on this, this research examines the medical risks to patients who experience losses caused by health workers. This research is normative juridical, that is, it refers to theories and regulations which aim to find out what the medical risk is to patients who experience harm caused by health workers to patients, causing their hands to swell. The research carried out is normative legal research, using a normative juridical legal research approach. The nature of the research used in completing this research is a qualitative approach, namely the data presented is in the form of information in the form of sentences or descriptions. The data source used is data originating from Islamic law, namely the Al-Qur'an and Hadith. The data collection tool used is observation Based on the results of the research and discussion, the conclusion is that a treatment or medical action is very dependent on many factors, therefore not every medical action that results in death or serious disability is not always called malpractice which must be resolved through the courts using the articles in the Law. -Civil Law or Laws that regulate malpractice issues. The cause of the plaintiff's claim was that it was rejected in its entirety in the medical risk case because the defendant was able to prove that the incident was not an unlawful act or malpractice but rather a medical risk that no one could take responsibility for.